Estudo bibliométrico sobre opções reais no Brasil - Costa, Brener Elias da (2014)
The efficiency of traditional methods of evaluation started to be questioned because they couldn t consider possible unsureness associated to investments. Discounted Cash Flow ( DCF ) methods ignore the value of options which appear in investment projects, specially those under high risk and unsureness. This way, uncertainty generates opportunities and the projects can be seen as options that may or not be exercised, including the strategy and management s flexibility as a benefit. Therefore, this theory emerges as an alternative to the analysis of decisions about real assets, complementing the traditional methods for investment s evaluation, providing to the managers the capacity to measure possible options about a project. In Brazil, as bibliographical survey, the model options, is used since 1989 and the legacy of Brazilian production is in quantitative and qualitative terms is unknown. This way, a descriptive or mapping inventory has been made, and later, in an analytical analysis, trying to comprehend the concepts and research that are guiding the Brazilian s bibliographic production about analysis of capital investment, through the Real Option s Theory ROT. The State of Art research method shown in this academic work goes through a systematic evaluation process of the academic works about ROT, published in Brazil from 1989, when the production in the country has started, until 2012. A survey about the brazilian production in master s dissertations and PhD theses has been made, achieving a total research of 202 cataloged works, Appendix A. Among the analyzed variables are: Research s nature and conceptual basement; device for measure and data gathering; type of analysis from the applied data; mathematic methods used; models for calculus of options and kinds of options. The balance of the entirety of studies allowed to evaluate its both qualitative and quantitative growth, point the most approached themes and departments, avoiding repetition, and knowing the different perspectives, approaches and applied methods, beyond tendencies and bias about the theme. It has been deduced that the Real Options Theory has not been yet disseminated in a expressive way, and the work s production is too concentrated in a few institutions and geographic regions; the focus of studies about options in real assets is centered in sequential and uncorrelated investments, mainly of application of Simulation-based methods and Dynamic Programming to the option s evaluation, like the Monte Carlo Simulation, binomial lattice models and binomial logarithmic methods; still, highlights itself the diversity of departments where the analyzed works were applied, and the primordial presence of departments where there is commercialization of underlying assets, as oil and mining. The plurality of approaches and both theoretical and methodological focus found inside the brazilian production reinforces the maturity reached by the theory, indicating that there is a diversified critic mass which is consistent to produce both a qualitative and theoretical leap in the brazilian productions.